Overcurrent limiting control with frequency fluctuation suppression under asymmetric faults for voltage source converters - Andong Liu; Jun Liu (International Journal of Electrical Power & Energy Systems)
Asymmetric faults are a common voltage fault in the power grid, with the rapid development of wind and photovoltaic power generation, grid-connected power generation systems based on voltage source converters (VSCs) will also be affected by asymmetric faults. Asymmetric faults can cause transient power imbalances and generate negative sequence components that have a negative impact on power quality. Therefore, it is necessary to limit overcurrent under asymmetric faults. At present, there are many studies on current limitations during faults, and it has a good inhibitory effect on overcurrent phenomena during faults. As is well known, during power grid faults, the voltage at the PCC will undergo sudden changes, and the frequency of the PCC will also change. Therefore, not only overcurrent needs to be suppressed, but frequency fluctuations also need to be suppressed. This article proposes a control strategy of positive and negative sequence variable virtual impedance control (PN-VVIC), generate positive and negative sequence impedances based on the magnitude of overcurrent and frequency fluctuations to enhance the ability to suppress transient overcurrent and frequency fluctuations, and proposes a power reference recalculation during faults to adjust the output power of VSC according to the severity of the fault, ensure no overcurrent during the fault, and inject reactive power into the power grid to assist in fault recovery. Subsequently, discuss the influence of the PN-VVIC’s parameters on VSC’s stability through small signal modelling and analyze VSC’s stability with the proposed method under asymmetric faults using phase portraits. Finally, the effectiveness of the control strategy proposed in this article is verified through experiments, and the experimental results are analyzed.